'Perhaps we may frighten away the ghost of so many years ago': Gaston Leroux's haunting of Andrew Lloyd Webber's The Phantom of the Opera. Issue 3 (1st December 2020) - Shah, Raj
This article investigates the ambivalent relationship between Andrew Lloyd Webber's 1986 megamusical The Phantom of the Opera and its 1910 source novel, Gaston Leroux's Le Fantôme de l'Opéra. Lloyd Webber and his collaborators initially differentiated the megamusical from previous adaptations by heralding a return to the spirit of Leroux's narrative. In doing so, however, Lloyd Webber lay down the limitations of his own creative authority over the material by establishing a 'knowing audience' primed to experience both the 'hypotext' of the novel and the 'hypertext' of the musical through the prism of the other. This article demonstrates how Leroux's novel was subsequently marginalized via a strategic project of displacement in the megamusical's 'paratexts', such as programme notes and media interviews. Examining these paratexts and Lloyd Webber's later reworkings of the material (as seen in its 2004 film adaptation and its 2010 sequel), this article argues that the composer-producer's attempts to appropriate the 'phantom' legend have been repeatedly disrupted by the novel's spectral resurgences in the public imagination.